Bile Acids in Gastroenterology : Basic and Clinical - Tazuma, Susumu; Takikawa, Hajime (Springer Japan : Imprint: Springer, 2017)
This book examines the biological aspects of bile acid analysis and their clinical applications, providing readers with an overview of cutting-edge discussions on Bile Acid research and diseases. It begins with detailed discussions on the biological aspects of bile acid, with chapters examining bile acid from various perspectives, from its metabolism to its use in therapeutic agents. Subsequent chapters focus on diseases involving bile acid abnormalities, and specific applications are addressed concerning gallstones, cholestatic liver disease, NAFLD/NASH, hepatitis, pancreatitis, esophageal cancer and colon cancer. In keeping with the book's integrated approach, the Editor has gathered a broad range of eminent scholars and practitioners to provide a comprehensive review of modern bile acid research. The book offers clinical physicians, basic researchers and postgraduate students essential insights into cutting-edge research and paves the way for further research.